2002
DOI: 10.1152/ajpheart.00561.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of shock-induced arrhythmogenesis during acute global ischemia

Abstract: Little is known about the mechanisms of vulnerability and defibrillation under ischemic conditions. We investigated these mechanisms in 18 Langendorff-perfused rabbit hearts during 75% reduced-flow ischemia. Electrical activity was optically mapped from the anterior epicardium during right ventricular shocks applied at various phases of the cardiac cycle while the excitation-contraction decoupler 2,3-butanedione monoxime (BDM; 15 mM) was used to suppress motion artifacts caused by contraction of the heart. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…Several studies using optical mapping have demonstrated that APD is shortened during low flow ischemia. [27][28][29] However, in the current study, we induced global ischemia. Under these experimental conditions, our high resolution imaging device detected only weak change in fluorescence, therefore, we could not record the APD during ischemia.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies using optical mapping have demonstrated that APD is shortened during low flow ischemia. [27][28][29] However, in the current study, we induced global ischemia. Under these experimental conditions, our high resolution imaging device detected only weak change in fluorescence, therefore, we could not record the APD during ischemia.…”
Section: Discussionmentioning
confidence: 88%
“…Motion blockers were avoided because they might prevent alternans from being observed. Two laboratories have used di-4-ANEPPS to study defibrillation mechanisms in ischemic hearts treated with DAM (4,13,15). Ischemia still Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence imaging has been used to map Ca 2ϩ transient alternans during ischemia in the blood-perfused rabbit heart (30), and marked spatial heterogeneity was found. Optical methods have also been used to study the mechanism of electrical defibrillation in the presence and absence of ischemia in hearts taken from small mammals (4,13,15). For these studies, fully intact hearts were used, which were stained with di-4-ANEPPS and treated with the pharmacological motion blocker diacetyl monoxime (DAM).…”
mentioning
confidence: 99%
“…We compared the gradient of VEP (ٌVEP) at the end of the shock and the postshock conduction velocity (vc) between AR and DR waveforms. On the basis of our previous study (5), the total number of pixels with ٌVEP larger than 24 mV/mm was defined as the index of ٌVEP (NVEP), which served as a quantitative measure of ٌVEP generated by the shocks. Postshock vc was calculated from the maps of activation using a previously described algorithm (31).…”
Section: Methodsmentioning
confidence: 99%
“…Rabbit hearts (n ϭ 10) were Langendorff perfused, and AR and DR waveforms (7,20, and 40 ms) were randomly delivered from two line electrodes placed 10 mm apart on the anterior ventricular epicardium. We optically mapped cellular responses to shocks of various strengths (5,10, and 20 V/cm) and coupling intervals (CIs; 120, 180, and 300 ms). Optical mapping revealed that maximum virtual electrode polarization (VEP) was reached at significantly different times for AR and DR of the same duration (P Ͻ 0.05) for all tested CIs.…”
mentioning
confidence: 99%